MODERN METHODS OF COMMUNICATIVE ENGLISH TEACHING - Abdisattarova Marjona Sherzod qizi (TADQIQOTLAR, 2025)
Abstract This article explores the importance of modern communicative methods in teaching English, their effectiveness in the learning process, and their role in developing students’ language skills. It also examines interactive approaches such as role play, brainstorming, case study, and debate, and discusses their impact on students’ communication skills and motivation.